Peningkatan Motivasi Dan Hasil Belajar Bahasa Indonesia Melalui Model Pembelajaran PBL Siswa Sekolah Dasar - Dwi Kurniati Rofingah; Andri Anugrahana; Tri Utami (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The purpose of this research is to determine the influence of the Problem-Based Learning (PBL) instructional model on the motivation and learning outcomes of third-grade students in SD Kanisius Klepu. The study was conducted at SD Kanisius Klepu during the academic year 2022/2023. This research is a classroom action research with data collection techniques using student comprehension questionnaires and scores from worksheets (LKPD). The research went through the pre-cycle, cycle one, and cycle two stages using the PBL instructional model. Data collection was conducted during the pre-cycle and cycle two. The results obtained from this research showed an improvement in the scores of the LKPD from the pre-cycle to cycle two. The average score in the pre-cycle was 72, while the average score in cycle two reached 93. Furthermore, the analysis of data collected from the student comprehension questionnaires showed an improvement as well. This can be observed from the higher percentage in cycle two compared to the pre-cycle. In conclusion, "The PBL instructional model is effective in enhancing the motivation and learning outcomes of third-grade students in SD Kanisius Klepu."